Influence of duration of dietary vitamin E supplementation on swine growth performance and carcass quality - Stika, J.F.; Unruh, John A.; Kropf, Donald H.; Hunt, Melvin C.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Supplementing medium-lean genotype pigs with supranutritional concentrations of dietary vitamin E (91 IU d-a-tocopheryl acetate/lb of feed) for as long as 70 d during the finishing phase was not effective in improving swine performance, feeding characteristics, and 24 h loin muscle quality. However, lower carcass temperatures obtained by spray chilling pork sides at O°C versus 4.4°C had a beneficial effect on 24 h carcass quality by improving marbling and lean firmness scores and reducing loin muscle moisture exudate. Overall, 24 h pork carcass quality was impacted more by chill rate than dietary vitamin E supplementation.
Keywords: Swine; Pork; Vitamin E; Chill rate